2021
DOI: 10.3390/su131910597
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Internet of Things Technology Adoption Decisions and Pricing Strategies for High-Traceability Logistics Services

Abstract: The Internet of Things (IoT) technology-based tracking system can reduce freight loss/damage during delivery, thereby avoiding wasting social resources. In this study, we address the issue of whether an E-retailer with a logistics arm should provide high-traceability logistics value-added service (based on IoT technology) in two customer segments and analyze their pricing decision. We found that companies always adopt IoT when equipment operation cost is low and not when the cost is high. Otherwise, the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…There is an ongoing need to renew radio-frequency identification tags because they handle waste bins frequently, therefore operating expenses are increased, as well dynamic or automatic weight sensors could cause errors and consume more time than static or manual weighing method (Wen et al , 2018). Based on operating costs and internal efficiency, Zhang and Liu (2021) found that enterprises adopt IoT. In the foodservice industry, some of the challenges encountering the adoption of IoT are the high cost and the lack of accurate design algorithms regarding the available smart refrigerators (Jain et al , 2022).…”
Section: Review Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an ongoing need to renew radio-frequency identification tags because they handle waste bins frequently, therefore operating expenses are increased, as well dynamic or automatic weight sensors could cause errors and consume more time than static or manual weighing method (Wen et al , 2018). Based on operating costs and internal efficiency, Zhang and Liu (2021) found that enterprises adopt IoT. In the foodservice industry, some of the challenges encountering the adoption of IoT are the high cost and the lack of accurate design algorithms regarding the available smart refrigerators (Jain et al , 2022).…”
Section: Review Findingsmentioning
confidence: 99%
“…By using IoT technology-based tracking system, Zhang and Liu (2021) highlighted that cargo loss or damage could be avoided during delivery. By adopting IoT-based multitemperature delivery planning system, perishable food e-orders could be handled effectively.…”
Section: Ranking Of the Benefits Of Iot Adoption In Hospitality Researchmentioning
confidence: 99%
“…However, its distribution destination is limited, and it is preferable only for some large-size CBEC sellers (Sun et al, 2017) [12]. To settle the drawbacks, OWL emerges as its improvement and innovation of the existing cross-border logistics models with the application of new information technology [13], and OWL is used, especially for products with the characteristics of obsolescence, such as fashion items and 3C items (Giufrida et al, 2020) [14].…”
Section: Introductionmentioning
confidence: 99%
“…As for the operation of the OWL, it is subject to some regulatory barriers, customs clearance, foreign-language communication, and returns handling, in addition to shipping cost, delivery cost, and delivery options (Gomez-Herrera et al, 2014; Giufrida et al, 2020) [14,15]. International outsourcing of OWL is likely to increase, to handle e-commerce shipments (Morganti et al, 2014; [13,16], to reduce the risks of the investment in foreign market logistics assets, and clear the local knowledge barriers (Shi et al, 2016;Ren et al, 2020) [17,18], as well as to minimize operating costs and carbon emissions and to improve service level (Liu and Lyons, 2011; [19][20][21]. Here, we focus on an integrated OWL, which provides one-stop control and management service for frst-way transportation, warehousing, sorting, packaging, goods delivery, and customs declaration/customs clearance, established and operated by the third-party logistics provider, as well as supply chain optimization, goods identifcation, anticounterfeiting traceability (Lee and Yeon, 2021) [22], logistics real-time tracking, rapid response to consumer demand, customized solution, and other services (Wang, 2018) [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation